(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
Nowadays, aluminium (Al) exposure has been increasing and it has the potential to be toxic in animal and humans. In recent years, ginger has become a subject of interest because of its beneficial effects on human health. The purpose of the present study to investigate the effect of ginger extract on serum biochemical parameters of aluminium chloride (AlCl3) induced male rats. 24 Wistar rats (6 in each group) distributed into 4 groups. Control group received distilled water as vehicle; In E1 group, animal received AlCl3 orally (100 mg/kg bw), E2 group received AlCl3 (100 mg/kg bw) and simultaneously with ginger extract (50 mg/kg bw) and E3 group received ginger extract alone (50 mg/kg bw) for 60 days. At the end of the experimental period, blood samples were collected for separating the serum for biochemical analyses. The results showed that oral administration of aluminium revealed a significant increase in the levels of serum glucose, total protein, globulin, albumin, urea, uric acid, creatinine, lipid profile and serum aspartate aminotransferase (AST), alanine aminotransferase (ALT) and alkaline phosphatase (ALP) and no change was noted in bilirubin. The extract of ginger decreased the activities serum levels of AST, ALT, ALP, lipid profile and all the parameter studied. It was concluded that the consumption of ginger protects the liver and kidney against the Aluminium toxicity. In addition, ginger is capable of improving hyperlipidemia and the impaired kidney functions.